ELT Teachers’ Difficulties at Elementary Schools in Rural Area - Mulyadi Syahputra (Almufi Jurnal Pendidikan, 2022)
This study highlights the difficulties of teaching English at primary level in rural areas of Aceh. The participants of the research were from Pining District, Gayo Lues, Aceh, Indonesia. Data was collected from twenty primary teachers including both male and female of government schools and the interview was conducted to two teachers randomly taken from the participant of the survey. Data was analyzed on SPSS version 25. A questionnaire gave to the teachers to express their views about difficulties of teaching English at elementary level in rural areas. The teachers described their difficulties related to socio cultural difficulties, students’ lack of prior knowledge, students’ lack of motivation, schools’ lack of facilities and teacher’ lack of training on their professionalism.